The regulation of medical devices and the role of the Medical Devices Agency - Jefferys, D B (Blackwell Science Inc, 2001)
This article reviews the regulation of medical devices in the UK and Europe and compares the regulatory regime with that for pharmaceuticals. The regulation of devices follows the ‘New Approach’ policy of the EC Commission and involves more self-regulation and conformity assessment. The controls are relatively recent beginning in 1993 for Active Implantable Devices and concluding with the In Vitro Diagnostic Directive implemented in June 2000. The article describes how the directives have been implemented in the UK, the role of the Notified Bodies and the role of the Medical Device Agency (MDA) as the competent authority. In particular the Agency's compliance and standards work is described along with the strategy and post marketing surveillance and adverse incident scheme. The MDA is a key international device regulatory agency and its international role is discussed. So too is its device evaluation programme for the NHS and how this complements the work of NICE. The article also considers the future direction of the MDA and changes in the device sector.